ОГРАНИЧЕНИЯ ВЕКТОРА ИЗМЕРЯЕМЫХ КООРДИНАТ В ЭЛЕКТРОМЕХАНИЧЕСКИХ СИСТЕМАХ НА ОСНОВЕ БЕСКОНТАКТНЫХ ДВИГАТЕЛЕЙ С ПОСТОЯННЫМИ МАГНИТАМИ - Акинин, К.П. (Інститут електродинаміки НАН України, Київ, 2011)
Designing features of the electromechanical systems on the basis of permanent magnet brushless motors are considered. Variants of control of field orientation with limitation of vector of measured coordinates are investigated. Variants of rotor rotation angle function for formation of signals of angular position and rotation frequency are given. References 12, figures 2.